DEVELOPMENT OF EFFECTIVE VACCINES FOR OLD MICE IN A TUMOR MODEL - Posnett, David N (Vaccine, 2008)
Vaccines are often inefficient in old people and old mice. Few studies have focused on testing vaccines in old populations. Here we used DNA tumor antigen vaccines against melanoma and showed that old mice were not protected. Vaccines incorporating fusions of the tumor antigen with microbial adjuvant proteins OmpA (E. Coli) or Vp22 (Herpes simplex virus-1) dramatically improved protection of old mice. The mechanisms by which these adjuvant proteins act are distinct. TLR2 was not required for either OmpA or Vp22. Antigen processing and presentation were not boosted by these fusion constructs. However, fusion constructs with Vp22 gave a strong CD4 response to B16 melanoma and the OmpA response is MHC-II dependent. Both adjuvant fusion constructs stimulated CD4 and CD8 responses otherwise diminished in old mice.